Pengaruh Penggunaan Bahan Ajar Biologi dengan Pendekatan Contextual Teaching and Learning (CTL) pada Materi Ekosistem Terhadap Hasil Belajar Siswa - Nuhuyanan, Yuliana; Seknun, M. Faqih (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2023)
Teaching materials are a set of subject matter that is arranged systematically displaying the integrity of the competencies that will be mastered by students in learning activities. Teaching materials can help teachers in delivering learning materials, so that learning objectives can be achieved. This study aims to determine the effect of the use of biology teaching materials with a Contextual Teaching and Learning (CTL) approach on ecosystem materials on the learning outcomes of grade VII MTs Al-Hilaal students. This type of research is quantitative descriptive with a sample of 32 people. The instruments used are questionnaires and test questions. The data analysis technique used uses simple linear regression analysis by first conducting a pre-requisite analysis test, namely the data normality test and the data homogeneity test. Based on the results of data analysis, it is known that there is a significant influence on the use of biology teaching materials with a Contextual Teaching and Learning (CTL) approach on ecosystem materials on the learning outcomes of grade VII MTs Al-Hilaal Katapang students. The influence of the use of biology teaching materials with a Contextual Teaching and Learning (CTL) approach on ecosystem materials on the learning outcomes of grade VII MTs Al-Hilaal Katapang students, West Seram Regency, is 59.20% and the remaining 40.80% is influenced by other factors.